2018
DOI: 10.12659/msm.906528
|View full text |Cite
|
Sign up to set email alerts
|

Butein Inhibited In Vitro Hexokinase-2-Mediated Tumor Glycolysis in Hepatocellular Carcinoma by Blocking Epidermal Growth Factor Receptor (EGFR)

Abstract: BackgroundAnaerobic glycolysis is an important physiological process of all cancer cells. Butein has been reported to demonstrate substantial antitumor activities in various cancers. However, the effect of butein on tumor glycolysis remains unclear. In this study, the effect of butein on tumor glycolysis and the underlying mechanism were investigated in hepatocellular carcinoma (HCC).Material/MethodsCell proliferation assay and anchorage-independent growth assay were carried out to evaluate the antitumor activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…The half maximal inhibitory concentration of butein in NSCLCCs was found to be 61.8 mM at 24 h. We have chosen the concentration butein based on the present and previously reported studies. 16,40 To our surprise, we observed that, irrespective of different concentrations of glucose, butein showed similar anticancer activity. In liver cancer cells, butein has shown its anticancer activity through the inhibition of HK II activity, 40 which is overexpressed in different solid tumors as well.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The half maximal inhibitory concentration of butein in NSCLCCs was found to be 61.8 mM at 24 h. We have chosen the concentration butein based on the present and previously reported studies. 16,40 To our surprise, we observed that, irrespective of different concentrations of glucose, butein showed similar anticancer activity. In liver cancer cells, butein has shown its anticancer activity through the inhibition of HK II activity, 40 which is overexpressed in different solid tumors as well.…”
Section: Discussionmentioning
confidence: 65%
“…16,40 To our surprise, we observed that, irrespective of different concentrations of glucose, butein showed similar anticancer activity. In liver cancer cells, butein has shown its anticancer activity through the inhibition of HK II activity, 40 which is overexpressed in different solid tumors as well. Further, this enzyme is also overexpressed in anaerobic glycolysis.…”
Section: Discussionmentioning
confidence: 65%
“…For instance, Yang et al, (2018) reported that butein reduced the viability of cervical cancer cells through a proapoptotic effect by blocking inhibitor of apoptosis (IAP) proteins and activating extrinsic as well as intrinsic proapoptotic cascades. Further, it inhibited the proliferation and survival of HCC ells effectively (Liao et al, 2018;Zhou et al, 2018). In addition, butein was also reported to exert its antiproliferative and pro-apoptotic effect through inhibition of NF-κB, AP-1 and Akt signaling in HTLV-1infected T cells in both in vitro and in vivo settings clearly indicating its therapeutic potential against adult T-cell leukemia/lymphoma (Ishikawa et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, the preceding reports have also suggested the same activities against different cancer cells such as breast, blood, liver, cervical etc. (Yang et al, 2012;Liao et al, 2018;Tang et al, 2016;Yang et al, 2018). For instance, Yang et al, (2018) reported that butein reduced the viability of cervical cancer cells through a proapoptotic effect by blocking inhibitor of apoptosis (IAP) proteins and activating extrinsic as well as intrinsic proapoptotic cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Butein suppresses the cell viability of non‐small cell lung cancer through ER stress‐dependent ROS generation and apoptosis pathway 31 . Butein inhibits cell proliferation and glycolysis in hepatocellular carcinoma through suppressing epidermal growth factor receptor (EGFR) signaling pathway 36 . Butein suppresses migration and invasion of cancer cells through inhibiting the activity of matrix metalloproteinases 2 (MMP‐2) and metalloproteinases 9 (MMP‐9), and the expression of vascular endothelial growth factor (VEGF) 37,38 .…”
Section: Discussionmentioning
confidence: 99%